Complete mitochondrial genome of Pisaura bicornis (Araneae: Pisauridae) and its phylogenetic implications - Shu-Yan Yan; Kang-Kang Xu; Da-Xing Yang; Can Li; Wen-Jia Yang (Mitochondrial DNA. Part B. Resources, 2019)
The complete mitochondrial genome of Pisaura bicornis (GenBank accession number MN296112) is 15,281 bp in length and contains 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), 2 ribosomal RNA genes, and a putative control region. The overall base composition of this genome is A (35.65%), C (8.12%), G (13.47%) and T (42.76%), demonstrating an obvious bias of high AT content (73.2%). ATT, ATA, TTG were initiation codons and TAA, TAG, and T were termination codons. Ten tRNAs (trnD, trnF, trnG, trnH, trnK, trnP, trnR, trnT, trnY, and trnE) lacked the TΨC arm stem, while three tRNAs (trnA, trnS1, and trnS2) lost the dihydrouracil (DHU) arm. Phylogenetic tree based on 13 PCGs showed that P. bicornis is closely related to Dolomedes angustivirgatus and belongs to Pisauridae.